Review of misconceptions in physics among Indonesian high school students: Diagnosis, causes, and remediation - Dendy Siti Kamilah; Beata Graceshela Muki; Lina Aviyanti; Andi Suhandi (Momentum: Physics Education Journal, 2025)
Misconceptions in physics education pose significant challenges to student learning and conceptual understanding. This research aims to bridge gaps in understanding by systematically identifying and analyzing the diagnostics, causes, and remediation methods for misconceptions in physics among Indonesian high school students. Using a Systematic Literature Review (SLR) following the PRISMA method, 61 articles were selected from databases such as Scopus and Google Scholar, focusing on publications between 2019 and 2024. The results reveal that static fluids emerged as the most frequently studied topic in misconception research, with common issues including the misunderstanding of buoyancy and hydrostatic pressure. Diagnostic tools were dominated by four-tier tests, which offer high accuracy and ease of analysis compared to other methods. The findings also highlight that the primary causes of misconceptions are rooted in students' intuitive thinking and teaching methods. Computer simulations were identified as one of the most effective remediation strategies, often employed alongside conceptual change texts and laboratory-based approaches. This study consolidates existing research and provides actionable insights for educators by highlighting effective diagnostic tools and strategies to design targeted interventions, foster deeper conceptual understanding, and improve learning outcomes in physics education.